Designing Wemos and GPS-based Wireless Communication Gloves to Prevent Group Members from Getting Lost - Achmad Alfath Pratama; Nina Paramytha; Endah Fitriani; Rahmat Novrianda Dasmen (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
Group travel in densely populated areas presents risks of losing members, especially during peak periods such as weekends. This study aims to develop a wireless communication glove device as an aid for inter-member detection to prevent loss during travel. The method involves designing a device based on the Wemos microcontroller integrated with GPS sensors for position tracking, MAX30100 heartbeat sensor for health monitoring, an OLED I2C display as visual interface, and a buzzer as alarm. The system functions by identifying unique IDs between devices within a certain radius and triggers an alarm when connection is lost. Testing results indicate the heartbeat sensor accuracy with an average deviation of less than 3 bpm compared to manual measurements. Maximum connection distance without physical obstacles ranges from 24 to 26 meters, decreasing to 18 meters with wall obstructions. The master device detects connection loss within approximately 20 seconds, indicated by an audio alarm and display changes on the OLED screen. The estimated operational duration is 5.5 hours at 2.4 Watts power consumption. Overall, this device effectively prevents member loss with simple health monitoring and reliable connection detection features.